Scientific and economic comparison of outdoor characterisation methods for photovoltaic power plants. (April 2019) - Mühleisen, W.; Hirschl, C.; Brantegger, G.; Neumaier, L.; Spielberger, M.; Sonnleitner, H.; Kubicek, B.; Ujvari, G.; Ebner, R.; Schwark, M.; Eder, G.C.; Voronko, Y.; et al.
Abstract: Over the last years, the development of innovative, fast and non-destructive characterisation techniques for the detection of PV-module failures and advanced analysis of yield losses in photovoltaic power plants has become a key challenge in scientific research. Besides standard on-site thermographic screening, several novel and easily applied methods were developed and successfully tested. They differ mainly in their possible field of application, their applicability in the detection of different failure types and their cost of setup and operation. In order to evaluate the boundary conditions of application for the various methods, different defective PV-modules were comparatively investigated with commercially available and innovative outdoor analysis methods. The results were evaluated with regard to error detection rate and economics. Based on this comparison, efficient operation and maintenance (O&M) measures for early and general failure detection within large power plants can be deducted. Highlights: A systematic comparison with help of most known inspection devices was done on faulty PV modules on site. A comprehensive analysis of standard PV module failures resulted in a decision matrix. With only one inspection method, not all faulty PV modules can be found. The usage of multiple inspection devices is a requirement to classify a failure correctly.